PERLAKUAN AKUNTANSI TERHADAP MAIN PRODUCT DAN BY PRODUCT SERTA PENGARUHNYA TERHADAP LABA PERUSAHAAN (STUDI KASUS PADA PABRIK TAHU DAN TEMPE MUN KOTA MUARADUA SUMATERA SELATAN) - Yesi Permata Sari; Suyanto Suyanto; Yulita Zanaria (Jurnal Akuntansi AKTIVA, 2021)
The study aims to determine the accounting treatment of company profit at the tofu and tempe factories muaradua city, south sumatra. This data pf obtained from interviews and documentation, rrsearch data was carried using qualitative describtif data analysis,namely ricogenition, easurementh and presentation. The result of this data indicate that the tofu and tempe factoties muaradua city south sumatra calculate in main product and by product using market values of reversals. In the metode calculation of market value it can be seen that the production cosh by product sales increase the company profit by Rp.24.273/kg. Therefore,by product sales increase the comlany profit By Rp. 238,551,310.